Renoprotection of Microcystin-RR in Unilateral Ureteral Obstruction-Induced Renal Fibrosis: Targeting the PKM2-HIF-1α Pathway - Ren, Yan; Wang, Jie; Guo, Wenwen; Chen, Jingwen; Wu, Xin; Gu, Shubo; Xu, Lizhi; Wu, Zhiwei; Wang, Yaping (Frontiers in Pharmacology, 2022)
Renal fibrosis is a pathological characteristic of the endpoint of chronic kidney disease (CKD), which remains a major public health problem. None of the current therapies is effective in stopping kidney fibrosis progression. In light of our novel detection of a potential antifibrosis of microcystins (MCs), we investigate the renoprotection effect of MCs with UUO-induced renal fibrosis. The treatment of MCs was initiated in model animals in advance of UUO operation. After determining that the antifibrotic effect of MCs was independent of its toxicity, our study focused on the renoprotection of microcystin-RR (MC-RR), a lower toxic congener of MCs, in UUO mice and the cell models in vitro. The co-immunoprecipitation assay and recombination plasmid transfection were used in the investigation of the mechanism of antifibrosis of MC-RR. The data show that MC-RR substantially exerts an effect on renoprotection with suppression of the expression of TGF-β1/Smad signaling molecules and a blockage in epithelial dedifferentiation and myofibroblast activation in UUO model animals. MC-RR shows a binding directly to pyruvate kinase M2 (PKM2), downregulates PKM2-HIF-1α signaling, restores the inhibited expression of MMP-7 and MMP-13, and reduces the upregulated expression of MMP-9 in UUO renal tissues. The current study demonstrates a novel effect of MC-RR on renoprotection in kidney damage, which could be conducted in therapeutics for chronic kidney disease.